Vrednotenje zahtevnejših geografskih učnih vsebin na vseh ravneh izobraževanja - Resnik Planinc, Tatjana (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2002)
The article deals with a didactical problem of transfer and understanding of more demanding geographical contents which are included into geographical educational vertical. Further improvement of geography teaching and assurance of high quality syllabus on every level of geographical education require a defining of more demanding geographical contents and reasons for their difficulty, argumentation of their incorporation into syllabuses and assessment of ways and methods for dealing with them and for their adoption. The analyses of scientifically demanding geographical contents offer the origins for better organisation of contents in the vertical of geographical education and the origins for better education of future geography teachers.
Keywords: didactic method; didaktika; geografija; geography; metodika; pouk